The political economy of Eurasian regionalism / Kairat Moldashev - Kairat, Moldashev (2015)
The regional integration process among the post-Soviet states is a source of rich empirical data for regionalism scholars and a difficult puzzle at the same time. The interest in the region increased in the beginning of the 1990s when various theories were generated and tested, but, after a decade of ink-on-paper regional agreements, some analysts concluded on the failure of regional arrangements among the post-Soviet states. However, the recent developments, such as the establishment of the Belarus, Kazakhstan, and Russia Customs Union in 2010 and the Eurasian Economic Union in 2015, renewed the interest of the scholars and policy-makers in the integration processes in the region. The key purpose of the study is to understand the motives of the various actors (i.e., political elites, businesses, nationalist forces) involved in the process of region-building in Central Eurasia. It is argued that the application of the rationalist approaches based on material incentives is not sufficient to understand the choices of the actors to support or oppose the Eurasian regionalism project, and one should consider ideational factors that inform the actors’ preferences. The study builds on the contemporary critical constructivist theories and the New Regionalism Approach in particular, which view regionalism as a political landscape under construction that is characterised by several interrelated dimensions and a variety of actors. In exploring the motives of the actors in Belarus, Kazakhstan, and Russia, the study distinguishes among three main interrelated dimensions of Eurasian regionalism: regionalism as a trade bloc; developmental regionalism; and regionalism as an identity project.